High-energy dissipative soliton with MHz repetition rate from an all-fiber passively mode-locked laser - Jiang, Kai (2013)
We experimentally demonstrate pulse energy enhancement in an all-fiber passively mode-locked laser operating in the large normal dispersion regime. By increasing the laser cavity length as well as its net cavity dispersion, the proposed laser, which is mode-locked by nonlinear polarization rotation, generates highly chirped dissipative solitons with pulse energies up to 9.4 nJ. The fundamental repetition rate is 2.3 MHz, and the pulse duration is 35 ps. Such low repetition rate as well as wide pulse width makes this mode-locked all-fiber laser a suitable oscillator to directly seed a fiber amplifier, which can be used as compact sources for high-power applications.